1988
DOI: 10.1139/f88-202
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate Analysis of Correlations Between Environmental Parameters and Cadmium Concentrations in Hyalella azteca (Crustacea: Amphipoda) from Central Ontario Lakes

Abstract: 1988. Multivariate analysis of correlations between environmental parameters and cadmium concentrations in Hyalella azteca (Crustacea: Amphipda) from central Ontario Bakes. Can. j. Fish. Aquat. Sci. 45: 1705-1 75 0.Cadmium concentrations in Hyalelda azteca collected from 69 central Ontario Bakes ranged from 8.1 3 to 56.6 kg/$ dry mass. Principal components analysis followed by multiple linear regression found three principal components, interpreted as water hardness, total cadmium, and dissolved organic carbon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1
2

Year Published

1990
1990
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 13 publications
(6 reference statements)
0
27
1
2
Order By: Relevance
“…At the end of the experiments the surviving amphipods were dried at 60 OC, and digested as described in Borgmann et al (1991) using the procedure of Stephenson & Mackie (1988). Twenty-five p1 of 70% nitric acid was added to 1 to 4 amphipods (0.5 to 2 mg dry weight), and allowed to sit for 1 week.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the end of the experiments the surviving amphipods were dried at 60 OC, and digested as described in Borgmann et al (1991) using the procedure of Stephenson & Mackie (1988). Twenty-five p1 of 70% nitric acid was added to 1 to 4 amphipods (0.5 to 2 mg dry weight), and allowed to sit for 1 week.…”
Section: Methodsmentioning
confidence: 99%
“…It can also be readily collected in the field for studies on metal levels in wild populations (e.g. Stephenson & Mackie, 1988). It should, therefore, be a useful organism for elucidating the relative contributions of different metals to toxicity, both in the field and in laboratory assays (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Excluding data for Raft Lake where only two animals were sampled, Cd concentrations in H. azteca ranged from 0.46 to 12.5 μg g −1 dry weight. Stephenson and Mackie (1988) reported that Cd concentrations in H. azteca from central Ontario lakes ranged from 0.13 to 37.3 μg g −1 dry weight. The authors also reported from 1984 sampling in Richard, McFarlane and Kakakiwaganda Lakes that Cd concentrations in H. azteca were 17.8, 12.3 and 5.12 μg g −1 dry weight, higher than the current results of 11.0, 4.0 and 4.5 μg g −1 dry weight respectively, indicating a significant reduction after 14 years.…”
Section: Metal Concentration In H Aztecamentioning
confidence: 99%
“…Metal uptake is also related to water quality, including hardness and pH (Wang, 1987). Working in distilled water avoids interactions between Cd and other cationic ions, such as Ca> and Mg>, which may compete with Cd for biological sites, and anionic ions such as CO\ , which may coprecipitate with Cd, reducing its bioavailability (Stephenson and Mackie, 1988).…”
Section: Acute Toxicity Tests Revealed CD Lcmentioning
confidence: 99%